Adaptive Governance Strategy for Forest Conservation in Sumatra in Balancing Environmental Needs and Community Involvement - Julia, Indira Ratu (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study investigates the efficacy of adaptive governance strategies for forest conservation in Sumatra, that specialize in Lubuk Beringin village. Subjects and Methods: Through a combined-techniques technique, such as surveys and interviews, stakeholders' perceptions and studies have been analyzed. Results: Results reveal that network participation and institutional preparations considerably have an impact on stakeholders' perceptions of forest conservation. Conclusions: The findings emphasize the importance of bendy governance frameworks in fostering collaboration and resilience. Moving forward, promoting neighborhood empowerment and multi-stakeholder partnerships is crucial for sustainable forest management.